2016
DOI: 10.1016/j.cogdev.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Parental reminiscing style and children’s suggestibility about an alleged transgression

Abstract: We examined the links between parental elaborativeness and children's suggestibility about a salient event, testing the hypothesis that, in an accuracy-focused context, children of elaborative parents are more resistant to false suggestions than children of less elaborative parents. Our hypothesis was supported: in a sample of 68 4-7 year-old children and caregivers, parent elaborativeness, along with children's working memory, additively predicted resistance to false suggestions from an unfamiliar interviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…In addition, the accuracy of children’s memory during the forensic interviews and of mother–child reminiscing was not evaluated in this study. Laboratory research suggests that elaborative maternal reminiscing promotes accuracy and mitigates children’s suggestibility (Klemfuss et al, 2016) but may hinder the reliability of children’s reports if mothers introduce inaccurate postevent information (Lawson et al, 2018; Principe et al, 2017). Future research examining associations between maternal reminiscing and the accuracy of children’s reports in contexts that approximate those to which children testify would further inform the understanding of children’s autobiographical memory and recommendations for interviewing children.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the accuracy of children’s memory during the forensic interviews and of mother–child reminiscing was not evaluated in this study. Laboratory research suggests that elaborative maternal reminiscing promotes accuracy and mitigates children’s suggestibility (Klemfuss et al, 2016) but may hinder the reliability of children’s reports if mothers introduce inaccurate postevent information (Lawson et al, 2018; Principe et al, 2017). Future research examining associations between maternal reminiscing and the accuracy of children’s reports in contexts that approximate those to which children testify would further inform the understanding of children’s autobiographical memory and recommendations for interviewing children.…”
Section: Discussionmentioning
confidence: 99%
“…When parents discuss shared experiences with their children, there is an opportunity for the pair to "co-construct" a narrative, with the parent scaffolding the child's creation of their personal past and their identity through a life story (Vygotsky 1978). These skills, which are consistently practices, are then internalized by children leading to enhanced performance on independent memory tasks, such as more detailed and coherent autobiographical narratives (Reese and Newcombe 2007), and a stronger resistance to suggestive influence (Klemfuss et al 2016) However, individuals naturally differ in the styles and techniques they use when conversing with their children (Fivush and Fromhoff 1988;Sales et al 2003). One such difference is the level of elaboration utilized by parents ; .…”
Section: Parent-child Discussionmentioning
confidence: 99%
“…Melinder et al (2006) also used a ToM composite score based on two ToM tasks with two sub-tasks each, and found that the negative association between ToM and interrogative suggestibility was no longer apparent after controlling for age and executive function skills. Klemfuss et al (2016) used a single measure of ToM and found no association with children's interrogative suggestibility. Bright-Paul et al (2008) created a ToM composite measure from six ToM tasks and found, across two experiments, that ToM predicted resistance to suggestion in a misinformation paradigm even when controlling for both age and verbal mental age.…”
Section: Theory Of Mindmentioning
confidence: 94%
“…Theory of Mind (ToM) has been defined as the cognitive ability to understand that people can have different mental states than one's own, and this skillset is typically acquired by five years of age (Astington, 1993). The findings regarding the links between ToM and suggestibility are somewhat mixed across five experiments in four separate manuscripts (Bright-Paul, Jarrold, & Wright, 2008;Karpinski & Scullin, 2009;Klemfuss, Rush, & Quas, 2016;Melinder, Endestad, & Magnussen, 2006). In four of the five experiments ToM was assessed via a battery of tests.…”
Section: Theory Of Mindmentioning
confidence: 99%